Transcending the "peace vs. justice" debate: a multidisciplinary approach to transitional justice (sustainable peace) in Northern Uganda after the International Criminal Court’s involvement in 2004 - Nielsen, Magnus Rynning (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.